Individuals, organizations and careers : a relational perspective - Kyriakidou, Olympia; Özbilgin, Mustafa (Career development international, 2004)
The papers in this special edition were presented at the symposium, "Current developments in human resource management and organizational behaviour", organized at the University of Surrey, School of Management on 22 May 2003. What emerged at this symposium was the significance of "relationships" both within and around organizations as well as between communities of academics, practitioners, and consultants in understanding the development of careers and career contexts such as organizational forms, institutional structures and networks. In order to map out a way to study careers and career con.